A Field Report on Self-screening Visual Acuity Using a Computerized Vision Screener - Menozzi, M. (Klinische Monatsblätter für Augenheilkunde, 2013)
Background: Large-scale examinations are costly and time consuming. Costs could be reduced by asking patients to carry out tests by themselves. This study aimed to gain practical experience on how patients handle self-administered acuity tests.Material and Methods: We developed two computerized self-test acuity screening devices consisting out of a commercially available vision screener, an answering box and a PC. The answering box served to record the responses of the participants and to present verbal instructions to the participants. Participants took acuity tests for far (5 m, OS, OD, OU) and an acuity test for near (40 cm, OU) using the self-test screener. For the reason of privacy personal data like age, gender and habitual correction was entered on a separate PC. The devices were installed in two different locations and run without supervision.Results: Personal data records of 2528 participants (4 % women) were collected in both locations. The age in 45 % of the participants ranged between 41 and 50 years. 31 % of the participants declared to wear spectacles and 3 % contact lenses. 66 % of participants declared not to need a correction. A total of 1078 participants completed four acuity tests (OD far, OS far, OU far, OD near) using the self-test screening device. Depending on the acuity test and location, the average duration required to complete one acuity test ranged between 29.7 s to 39.1 s. The total duration for completing the four acuity tests was on average 133 ± 46 s.Conclusions: The duration for completing the acuity tests is considered as being short. Made experience speaks in favor of feasibility of self-tests in acuity screening.
Keywords: computerized vision test; screening; self-test; acuity; occupational medicine; health campaign